xxxx - Amalinda Savirani (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2007)
This paper investigates dilemas faced by local executives in promoting effectiae local governance while at the same time upholding democratic principles. Based on field research in Bantul and Jembrana, two notorious regencies for it's innovations in public policy, this paper concludes that from the process perspective, the implementation of democratic principle such as participation, accountability and transparency are still far too behind. However, when it analyzed using the outcomes perspective, policy innovations in Bantul and lembrana meet the public demands successfuly.